Influence work discipline and punishment on employee performance - Fajar, Fitriani; Umban , Adi Jaya; Aeni , Fira Fitullah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of work discipline and punishment on employee performance. This study uses an associative quantitative approach using a questionnaire distributed to 100 samples with purposive sampling technique. The instrument testing in this study used validity and reliability tests, data analysis techniques used descriptive analysis.. The results of this study indicate that: (1) Work Discipline has a positive effect on employee performance, as evidenced by the t-count value of 3.194 and the regression coefficient has a positive value of 0.653; (2) Punishment has a positive effect on employee performance, as evidenced by the t-count value of 2.340 and the regression coefficient has a positive value of 0.348; and (3) work discipline and punishment have a positive effect on employee performance, as evidenced by the calculated F result of 8,532 with a significance of 0.000. (4) The magnitude of the effect of Work Discipline on Employee Performance is evidenced by the adjusted R square value of 0.132 indicating that the ability of the independent variable to explain the variation of the dependent variable is 13.2% and the remaining 86.8% is explained by other variables outside this research model.